Sigmund Freud explorer of the unconscious - Muckenthoupt, Margaret (New York, New York Oxford University Press, 1997)
A biography of the world-famous Austrian doctor who spent his life analyzing the mind and its illnesses.
Includes bibliographical references (pages 152-153) and index.
Keywords: Freud, Sigmund -- 1856-1939 -- Juvenile literature; Psychoanalysis -- Austria -- Biography -- Juvenile literature